Psychological well-being and posttraumatic growth in caregivers of cancer patients - Cormio, Claudia; Romito, Francesca; Viscanti, Giovanna; Turaccio, Marina; Lorusso, Vito; Mattioli, Vittorio (Frontiers in Psychology, 2014)
Introduction Although research has shown that many cancer patients report positive life changes following cancer diagnosis, there are few data in the literature related to PTG in caregivers of cancer patients. However, the few studies available have shown that this kind of positive changes can also be experienced by family members. The aims of this study were to explore PTG in caregivers of cancer patients and to investigate correlations between the Posttraumatic growth, psychological status and QoL of caregivers and those of patients, taking into account also clinical and socio-demographic aspects. Methods We enrolled 60 patient/caregiver pairs in the Department of Medical Oncology of the National Research Center ‘Giovanni Paolo II’ in Bari. Both patients and caregivers were assessed using the following scales: Posttraumatic growth Inventory (PTGI); Hospital anxiety and depression scale; Short Form (36) Health Survey (SF-36); ECOG Performance Status. Clinical and socio-demographic data were collected. Results Caregivers showed significantly higher scores than patients in the dimension of "personal strength". Furthermore, we found a significantly close association between anxiety and depression of caregivers with those of patients. Younger caregivers were better than older ones in terms of physical activity, vitality, mental health, and social activities. Although the degree of relationship with the patient has no significant effect on the dependent variables of the study, it was found that caregivers with a degree of kinship more distant to the patient have less physical pain than the closest relatives. Conclusion Results of the present study show that caregivers of cancer patients may experience post-traumatic growth as the result of their caregiver role. It would be interesting to investigate in future research which factor may mediate the presence of post-traumatic growth.